2015
DOI: 10.1159/000371489
|View full text |Cite
|
Sign up to set email alerts
|

ß<sub>3</sub>-Integrin Inhibits Lipopolysaccharide-Induced Autophagy in Cardiomyocytes via the Akt Signaling Pathway

Abstract: Objective: To investigate the role of β3-integrin in lipopolysaccharide (LPS)-induced autophagy in cardiomyocytes and its underlying mechanism. Methods: β3-Integrin expression in cardiomyocytes was up- or downregulated by adenovirus transfection or cyclic arginine-glycine-aspartic acid (cRGD) peptide treatment before LPS stimulation. The expression of autophagy-associated proteins (LC3-II, Beclin-1 and Bcl-2) and the activation of Akt were determined using Western blotting. Autophagosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…From a more general perspective, an inverse relationship between autophagy and integrin-dependent anchorage signalling has been proposed, implying that the autophagic machinery counteracts anoikis (detachment-induced apoptosis) (57). For instance, downregulation of integrin b3 resulted in upregulation of autophagy markers (58). In line, it was observed that blockage of aVb3 signalling results in inhibition of adhesion and concomitant activation of the autophagic machinery, manifested in increased MAP1LC3B expression (59).…”
Section: Functional Lir Motifs In Integrin B3 As Potential Linkage Ofmentioning
confidence: 87%
“…From a more general perspective, an inverse relationship between autophagy and integrin-dependent anchorage signalling has been proposed, implying that the autophagic machinery counteracts anoikis (detachment-induced apoptosis) (57). For instance, downregulation of integrin b3 resulted in upregulation of autophagy markers (58). In line, it was observed that blockage of aVb3 signalling results in inhibition of adhesion and concomitant activation of the autophagic machinery, manifested in increased MAP1LC3B expression (59).…”
Section: Functional Lir Motifs In Integrin B3 As Potential Linkage Ofmentioning
confidence: 87%
“…This indicates PI3K-Akt-mTOR signaling or similar pathways may be activated when integrin β3 is overexpressed. Studies have shown that integrin β3 upregulation inhibits the autophagic process in cardiomyocytes by activating Akt [41], suggesting that the expression status of integrin may affect cell autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a major outer membrane component of Gram-negative bacteria such as E. coli, and acts as a mediator of host responses that elicit intestinal endotoxemia and multiple organ failure, as well as a stimulator of autophagic signaling in cultured intestinal epithelial cells and other cell types [39,40]. Under normal physiological conditions, low levels of autophagy are maintained that play a vital role in host defenses against microbial infection [41].…”
Section: Discussionmentioning
confidence: 99%